Why non-native speakers sometimes outperform native speakers in agreement processing. Issue 1 (24th January 2023) - Lee, Eun-Kyoung Rosa; Phillips, Colin
Abstract: It is well-known that native English speakers sometimes erroneously accept subject-verb agreement violations when there is a number-matching attractor (e.g., *The key to the cabinets were…). Whether bilinguals whose L1 lacks number agreement are prone to such interference is unclear, given previous studies that report conflicting findings using different structures, participant groups, and experimental designs. To resolve the conflict, we examined highly proficient Korean–English bilinguals' susceptibility to agreement attraction, comparing prepositional phrase (PP) and relative clause (RC) modifiers in a speeded acceptability judgment task and a speeded forced-choice comprehension task. The bilinguals' judgments revealed attraction with RCs but not with PPs, while reaction times indicated attraction with both structures. The results therefore showed L2 attraction in all measures, with the consistent exception of judgments for PPs. We argue that this supports an overall native-like agreement processing mechanism, augmented by an additional monitoring mechanism that filters explicit judgments in simple structures.